2017
DOI: 10.1002/ep.12727
|View full text |Cite
|
Sign up to set email alerts
|

Exploring citizens' support for policy tools at the food, energy, water nexus

Abstract: The food, energy, and water (FEW) nexus is attracting the attention of scholars throughout the fields of engineering, biological sciences, and public policy, among others. However, one important piece missing from the research is an understanding of the types of FEW-related policies citizens support and the factors that drive public support for those policies. As reported in this article, data from a nationally representative survey of the adult U.S. population show that the public's support for different poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Knowledge about resource tradeoffs, and specifically the food–water–energy nexus, has been linked to greater policy support for equitable and efficient management of these resources [ 11 , 12 , 69 ]. The most common measures used in the environmental literature are perceived (i.e., subjective) and assessed knowledge.…”
Section: Values–beliefs–norms (Vbn) Theory and Correlates Of Fwe Tmentioning
confidence: 99%
See 3 more Smart Citations
“…Knowledge about resource tradeoffs, and specifically the food–water–energy nexus, has been linked to greater policy support for equitable and efficient management of these resources [ 11 , 12 , 69 ]. The most common measures used in the environmental literature are perceived (i.e., subjective) and assessed knowledge.…”
Section: Values–beliefs–norms (Vbn) Theory and Correlates Of Fwe Tmentioning
confidence: 99%
“…A number of studies have linked knowledge about policy-specific facts to public preferences [ 12 , 67 , 72 ]. In a study of Las Vegas residents, Salvaggio et al [ 67 ] found that factual knowledge about drought is significantly associated with water conservation measures.…”
Section: Values–beliefs–norms (Vbn) Theory and Correlates Of Fwe Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Some research focuses on psychological predictors of policy support. Bullock and Bowman () found that knowledge about nexus issues as well as broad concern for the environment was positively associated with citizens’ support for policy tools aimed at managing food, energy, and water resources. Similarly, Portney et al.…”
Section: Nexus Researchmentioning
confidence: 99%